THE DIFFERENCE BETWEEN OXYTOCIN MASSAGE AND WOOLWICH MASSAGE ON THE SMOOTHNESS OF BREAST MILK FLOW IN POST-TERM MOTHERS - Paryono, Paryono; Novita Wulandari; Lusinta Agustina (Medical Journal of Nusantara, 2025)
Background: Exclusive breastfeeding is the best food for babies given according to needs for 6 months. However, not all postpartum mothers immediately produce breast milk, so efforts are needed to increase the flow of breast milk in postpartum mothers. Efforts to increase the flow of breast milk include oxytocin massage and woolwich massage. Objective: To determine the flow of breast milk in postpartum mothers after being given oxytocin massage intervention, to determine the flow of breast milk in postpartum mothers after being given woolwich massage intervention, to determine the difference between oxytocin massage and woolwich massage on the flow of breast milk in postpartum mothers. Research Method: The type of research used was a pre-experimental two group pretest and posttest design. The sampling technique was quota sampling. 30 samples were obtained that met the criteria. The data analysis technique used was non-parametric statistics, the Wilcoxon test and the Mann-Whitney test. Research Results: The flow of breast milk in the oxytocin massage group averaged 8.00 and the woolwich massage group averaged 6.50. The results of the Mann-Whitney test for the oxytocin massage group had a mean rank of 21.03 while the mean for the woolwich massage group had a mean rank of 9.97. The test results showed a significance value (p) = 0.000 where the p value (0.000) <0.05 means that there is a difference in the provision of oxytocin massage and woolwich massage on the smoothness of breast milk in postpartum mothers in the work area of ​​the Trucuk II Klaten Health Center. Conclusion: There is a difference in the provision of oxytocin massage and woolwich massage on the smoothness of breast milk in postpartum mothers in the work area of ​​the Trucuk II Klaten Health Center